Risk of in House Cigarette Smoke Exposure to the Premature Birth in Denpasar City - Ni Ketut Noriani; I Wayan Gede Artawan Eka Putra; I Nyoman Mangku Karmaya (Universitas Udayana, 2015)
Background and purpose: Indonesia is ranked fifth in the world in term of premature birth prevalence, which is estimated 10-20%. This study aimed to find out risk of in house cigarette smoke exposure to premature birth in Denpasar. Methods: This study is a case control. Case is a mother experienced premature delivery, while the control is mothers who been registered in the same period with mature delivery. Samples either case or control were selected using systematic random sampling, which preceded by listing premature and mature birth in each puskesmas in 2013. Data analysed bivariate and multivariate using chi-square test and logistic regression. Results: Bivariate analysis showed no significant different of characteristic (age, education, occupation and parity status) between case and control group. However, significant different of ANC behavior and average of arm circumference were found between case and control. Multivariate analysis showed that the adjusted OR of tobacco smoke exposure at home after being controlled by ANC and upper arm circumference was 3.647 (95%CI: 1.683-9.903). Conclusion: In house cigarette smoke exposure increases significantly the risk of premature birth in Denpasar.